Utilization Exe-Learning in Development E-Teaching Module for Independent Curriculum in Learning Informatics Network Material Computer - Stefany, Evy Maya; Nisa, Alifia Zumrotul; Risnasari, Medika (research, training and philanthropy institution Natural Aceh, 2025)
Technology has been applied in various areas of life, including education. Technological advances provide students with more materials and lessons to help them learn more efficiently. One application that can be used to create e-learning modules that optimize digital media. In the Exe learning program, teachers can develop modules to add text, images, and videos and create multiple-choice questions. The development of learning media using the ADDIE model includes analysis, design, development, implementation, and evaluation, and it involves class X students of Computer Networks at SMKN 1 Sepulu as research subjects. Data was collected through observation, interviews and tests. Data analysis was carried out using descriptive and qualitative methods. Two expert validators, material experts and media experts, carried out the validation. The data collection technique uses a questionnaire. Validation results from material experts meet the requirements of 93%, which means they are very valid. The media expert results meet the requirements at 96%, which means they are valid. At the implementation stage, a trial was carried out. The results of field trials on 10th-grade Computer Network students showed that as many as 30 students obtained an average score of 92.6% with excellent qualifications, which means this media is easy for students to learn. The test results of EXE-based learning media show that the media is very suitable for use as a computer network learning medium and helps students in teaching and learning.